Perancangan Sistem Pakar Diagnosa Penyakit Hipertensi dengan Metode Certainty Factor dan Dempster Shafer berbasis Website: Studi Kasus Puskesmas Brambang, Diwek, Jombang - Basuki Rahmat; Agung Mustika Rizki; Muchammad Fadzillah Zain (Switch : Jurnal Sains dan Teknologi Informasi, 2025)
Hypertension is a common disease in society and can lead to serious complications if not properly managed. This study aims to design a web-based expert system to assist in diagnosing hypertension using the Certainty Factor and Dempster Shafer methods. The Certainty Factor method is used to measure the confidence level of reported symptoms, while the Dempster Shafer method combines information from various sources to generate more accurate decisions. The system is designed with a user-friendly interface to facilitate access for medical personnel and patients. The research results show that the Certainty Factor method achieved an accuracy 97,9%, while the Dempster Shafer method reache 96,4%. The accuracy difference of 1,4% indicates that the Certainty Factor method is more effective in handling the uncertainty of hypertension symptoms than the Dempster Shafer method.